Pediatric phalanx fractures: A retrospective study and review of the literature. (August 2022) - Schizas, Stephanie; Lutz, Nicolas; Vardar, Elif; Merckaert, Sophie; Zambelli, Pierre-Yves; Samara, Eleftheria
Purpose: Conventional radiography is frequently performed in pediatric patients in whom finger fractures are suspected. However, until now, the rate of positive findings of finger radiographic examinations in pediatric patients is unknown. This study aimed to evaluate the number of positive findings in the standard radiographic examinations of finger injuries in pediatric patients in a Level 1 trauma center systematically. Methods: We conducted a retrospective study on all children 0–16 years old admitted for acute finger injury in the Emergency Department of a University Hospital during the first semester of 2019 and received a radiographic examination. Their demographic characteristics, fracture pattern, and treatment were then analyzed and interpreted. Results: Out of 478 finger injuries reviewed in this cohort, 160 X-rays revealed positive for a fracture giving a fracture rate of 33.5%. More than half of them (51.9%) occurred in the age group of adolescents (11–16 years). Among all finger fractures, only 3.8% of them treated surgically. Conclusion: In this study, a relevant amount of standard finger radiographs revealed a low fracture rate and a rare operative indication of 3.8%. Therefore, indications for X-rays should be reviewed properly and alternative procedures should be discussed. Clinical decision rules should be developed and the necessary pathways must be implemented to minimize radiation exposure, waiting time, and costs. Level of evidence: level IV